2012
DOI: 10.1007/s11367-012-0397-8
|View full text |Cite
|
Sign up to set email alerts
|

A review of life cycle assessments on wind energy systems

Abstract: Purpose Several life cycle assessments (LCA) of wind energy published in recent years are reviewed to identify methodological differences and underlying assumptions. MethodsA full comparative analysis of 12 studies were undertaken (10 peer-reviewed papers, 1 conference paper, 1 industry report) regarding six fundamental factors (methods used, energy use accounting, quantification of energy production, energy performance and primary energy, natural resources, and recycling). Each factor is discussed in detail t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(49 citation statements)
references
References 40 publications
1
48
0
Order By: Relevance
“…Kubiszewski et al (2010) presents a meta-analysis of 119 different turbines from 50 different analyses between 1977 and 2006, where a vast majority assumed a 20-year life span. Davidsson et al (2012) looked at ten more recent LCAs of wind turbines and found similar tendencies. Dolan and Heath (2012) reviewed and harmonized 72 LCAs on wind turbines and concluded that 20 years was the most commonly cited lifetime estimate as well as a common design life for modern wind turbines.…”
Section: Wind Turbine Service Lifementioning
confidence: 82%
See 2 more Smart Citations
“…Kubiszewski et al (2010) presents a meta-analysis of 119 different turbines from 50 different analyses between 1977 and 2006, where a vast majority assumed a 20-year life span. Davidsson et al (2012) looked at ten more recent LCAs of wind turbines and found similar tendencies. Dolan and Heath (2012) reviewed and harmonized 72 LCAs on wind turbines and concluded that 20 years was the most commonly cited lifetime estimate as well as a common design life for modern wind turbines.…”
Section: Wind Turbine Service Lifementioning
confidence: 82%
“…While some expect that the recycling rates for metals used in electricity generation technologies will be higher due to expected high collection rates (Elshkaki and Graedel, 2013), others mentions different situations that could lead to materials not being recycled (Davidsson et al, 2012).…”
Section: Assessing Natural Resource Constraintsmentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from the different rated capacities and designs used in the Vestas studies, the major reason for the difference in results is the fact that recycling of materials in the decommissioning stage is not considered in this study. According to Davidsson et al (2012), the environmental impacts embodied in a wind turbine are reduced by approximately half through end-of-life recycling. This is highlighted in Tremeac andMeunier (2009) andChen et al (2011) where a 26-27% reduction in total environmental indicator values is observed.…”
Section: Comparison Of Results With the Literaturementioning
confidence: 99%
“…Wind power improves energy diversity and safeguards against fossil fuel price unpredictability, thus stabilizing electricity generation costs in the long term [2]. All energy systems for converting energy into usable forms have environmental impacts associated with them [3][4][5][6]. The production of renewable energy sources involves the consumption of energy and natural resources as well as the release of pollutants like every other production process [7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%